2015
DOI: 10.1002/ppsc.201500005
|View full text |Cite
|
Sign up to set email alerts
|

Hydrothermal Synthesis of Nickel Phosphate Nanorods for High‐Performance Flexible Asymmetric All‐Solid‐State Supercapacitors

Abstract: Ni20[(OH)12(H2O)6][(HPO4)8(PO4)4]·12H2O nanorods are successfully synthesized via a one‐pot hydrothermal reaction. A high‐performance flexible asymmetric all‐solid‐state supercapacitor based on the obtained Ni20[(OH)12(H2O)6][(HPO4)8(PO4)4]·12H2O nanorods (positive electrode) and graphene nanosheets (negative electrode) is successfully assembled. It is the first report of this nanomaterial applied for all‐solid‐state supercapacitors. Interestingly, a maximum volumetric energy density of 0.446 mW h cm−3 at a cu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
22
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 35 publications
(23 citation statements)
references
References 29 publications
1
22
0
Order By: Relevance
“…22 Besides metal oxides which are widely studied as pseudocapacitive materials, [23][24][25][26][27] limited research has shown that onedimensional (1D) phosphate materials can also be effective supercapacitive materials. Pang 30 which were made by hydrothermal method. Beneting from the high pressure and heating of hydrothermal reaction condition, the material showed good crystallinity and exhibited higher energy density compared to conventional carbon based materials.…”
Section: Introductionmentioning
confidence: 99%
“…22 Besides metal oxides which are widely studied as pseudocapacitive materials, [23][24][25][26][27] limited research has shown that onedimensional (1D) phosphate materials can also be effective supercapacitive materials. Pang 30 which were made by hydrothermal method. Beneting from the high pressure and heating of hydrothermal reaction condition, the material showed good crystallinity and exhibited higher energy density compared to conventional carbon based materials.…”
Section: Introductionmentioning
confidence: 99%
“…Nickel Phosphates : In the past few years, several studies have attempted to establish nickel phosphates as pseudocapacitive materials, because of their relatively high specific capacitance . Pramanik et al developed an effective way to prepare nanoporous nickel phosphates by thermolysis of the corresponding precursor materials.…”
Section: Metal Phosphidesmentioning
confidence: 99%
“…Remarkably, no obvious capacitance decrease took place for the electrode over 3000 cycles at 30.0 A g −1 , implying the excellent cycling stability. Zhao et al have presented a facile hydrothermal approach for producing VSB‐5 nanorods, which showed a high surface area of 488 m 2 g −1 . A flexible asymmetric all‐solid‐state supercapacitor (VSB‐5 nanorod as the positive electrode, and graphene nanosheet as the negative electrode) was shown with great performances and excellent mechanical flexibility.…”
Section: Metal Phosphidesmentioning
confidence: 99%
“…Although SCs have many advantages compared to rechargeable batteries and fuel cells, their low energy density limits practical applications. Recently, asymmetric SCs (ASCs) with battery‐type Faradaic electrodes showed promise as alternative to SCs . According to the equation E =( C × U 2 )/2, the energy density ( E ) increases when as either the device capacitance ( C ) or cell voltage ( U ) increases.…”
Section: Figurementioning
confidence: 99%
“…Recently, asymmetric SCs (ASCs) with battery‐type Faradaic electrodes showed promise as alternative to SCs . According to the equation E =( C × U 2 )/2, the energy density ( E ) increases when as either the device capacitance ( C ) or cell voltage ( U ) increases. Compared to symmetric SC devices, ASCs can significantly increase the operating voltage in aqueous electrolytes by combining voltage windows from two electrodes.…”
Section: Figurementioning
confidence: 99%